Lost on Venus : the thrilling story of two boys who land on the planet and explore a fantastic world - Patchett, Mary Elwyn, 1897-1972. (London : Lutterworth Press, 1954)
Two young space trainees are chosen to take a test flight over Venus, but their rocket crashes and they encounter dangerous alien wildlife in their struggle to survive until they are rescued.
Muir, M. A bibliography of Australian children's books
Keywords: Life on other planets -- Juvenile fiction; Wilderness survival -- Outer space -- Juvenile fiction; Science fiction; Venus (Planet) -- Juvenile fiction; Outer space -- Exploration -- Juvenile fiction